Are vitamin D levels in lupus patients associated with non-scarring alopecia? - Gundogdu, B.; Yolbas, S.; Yildirim, A.; Koca, S. S. (Clinical & Exper Rheumatology, 2015)
[Abstract Not Available]
11th International Congress on Systemic Lupus Erythematosus -- SEP 02-06, 2015 -- Vienna, AUSTRIA